Development and operation of a novel non-invasive opto-acoustic underwater fish observatory in Kiel Bight, Southwestern Baltic Sea - Gröger, Joachim P.; Cisewski, Boris; Badri-Hoeher, Sabah; Böer, Gordon; Boos, Karin; Clemmesen, Catriona; Cojocaru, Ala; Dauben, Verena; Hoeher, Peter A.; Lehmann, Andreas; Matz, Sebastian; Mehrtens, Hela; et al. (Frontiers in Marine Science, 2024)
This study presents a trilateral test array of new opto-acoustic Underwater Fish Observatories (UFOs) that were operated and tested in Kiel Bight as part of the “UFOTriNet” project. While hydroacoustic and optical techniques have so far been used individually to observe and monitor fish stocks, we present a coupled hybrid system consisting of an optical device intended to scan the near-field as a subsample of a spatially larger medium-to-far-field, scanned by an acoustical device. The optical device consists of two residual light amplifying camera modules able to detect and classify various marine species at a high resolution in the range of at max 4 meters in the study area. To compensate for this spatial limitation, the acoustical component consists of a 2D imaging sonar with a maximum range of 50 m, albeit with a lower resolution. Species affiliation, morphometric characteristics of fish and other marine organisms were stereo-optically detected and classified in the nearfield, blended with acoustical activity in medium to far range, and projected onto the entire insonified area using a hybrid algorithm. Through the synchronous acquisition of multiparametric abiotic and biotic data, UFO allows an automatic, continuous, and non-invasive long-term monitoring of various fish and other marine species and their habitats at regional hotspots. An 86-day multiparametric sample revealing an abrupt shift from a clupeid fish to a gelatinous plankton dominated regime in summer/autumn 2021 in Kiel Fjord is used to demonstrate the potential of UFO for various applications.